2007
DOI: 10.25011/cim.v30i3.1754
|View full text |Cite
|
Sign up to set email alerts
|

A Written Action Plan for Early Treatment of COPD Exacerbations: An Important Component to the Reduction of Hospitalizations

Abstract: patients and also by respiratory muscle limitation in 10% of the patients. Conclusions: Based on admission diagnosis of 40 patients, 90% were defined as subject to pulmonary rehabilitation and in 10% were receiving cardiac rehabilitation. They divided into three specific functional recovery programs: ventilatory function recovery program (60%), cardiac function recovery program (30%), respiratory muscles recovery program (10%). Background: In chronic obstructive pulmonary disease (COPD), leg muscle blood flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, it has been demonstrated that early treatment of an AECOPD can lead to faster recovery from symptoms, improved health status and reduced risk of hospital admission [26]. Other studies also suggest that patients who use selfmanagement action plans to promptly treat exacerbations have 40% fewer hospital admissions [1,27]. Health status has become important in the validation of specific treatments used for AECOPD not solely based on the prevention of the AECOPD but also on the time to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that early treatment of an AECOPD can lead to faster recovery from symptoms, improved health status and reduced risk of hospital admission [26]. Other studies also suggest that patients who use selfmanagement action plans to promptly treat exacerbations have 40% fewer hospital admissions [1,27]. Health status has become important in the validation of specific treatments used for AECOPD not solely based on the prevention of the AECOPD but also on the time to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We used exacerbation definition A as our primary definition, as this is the one most often used definition in COPD studies (it has, for instance, been used consistently in all East London Cohort study reports [1,4,18]). Definition B has recently been used in studies on the self-treatment of acute exacerbations [19,20]. The two event-based definitions were modified from recent landmark COPD trials [21][22][23].…”
Section: Texasmentioning
confidence: 99%